PATIENTS' PERCEPTIONS OF CONTINUITY OFCARE ACROSS PRIMARY CARE LEVEL AND EMERGENCY DEPARTMENTS - Mohammed Salem Manea Al-Thanyh Fahad fawaz alanazi . Yahya Hussain Ali majrashi., Khallufah Ahmed Khallufah Almaqadi, Hassan Yahya Ahmed Alzubaidi, Salah Abduh Salah Alhasnani, Maqboul Ahmed Hassan Alamri, Ali Alhussain Ali Alamri, Ali Ahmed Hussain Alzaylaee, Abdullah Hassan Saeed Alzialai, Ali Saeed Ali Alaklabi,; Ali Saeed Ali Alaklabi, (Chelonian Research Foundation, 2023)
Background: Healthcare coordination and continuity of care conceptualize all care providers and organizations involved in health care to ensure the right care at the right time. However, systematic evidence synthesis is lacking in the care coordination of health services. This study aims: To assess patients' perceptions of continuity of care (COC) across primary care level (PCL) and emergency departments (EDS) and to identify contextual and individual factors that influence this perception. Methods: A Crosssectional study design was conducted in five emergency departments in KSA. Participants 501 adult patients referred to the ED by their primary care physician (PCP). Patients with cognitive impairment or in critical condition were excluded. Results Patients perceived high levels of the three types of COC On an individual level, older patients showed a perception of higher levels of continuity. Lower levels of informational and management continuity were observed among patients suffering from chronic diseases and patients with a high level of education. Patients also perceived a redundancy of medical exams, in parallel to a high degree of accessibility between care levels. On an organizational level, three structural factors were identified as barriers to COC, namely, ED workload, suboptimal sharing information system and the currentfee-for-service payment system that encourages competition and hinders coordination between actors. Conclusion Healthcare services seem satisfying for patients and easily accessible. However, efforts need to be directed towards improving their efficiency. A stronger PCL is also needed to benefit the healthcare system by reducing overuse of emergency services. On the individual level, a more enhanced patient-centered approach could be beneficial in improving patients' experience of care. Keywords: Patients ' perceptions, Continuity of care, Primary care level, and Emergency department.